Prehension Deficits in Amblyopia - Grant, Simon; Melmoth, Dean R; Morgan, Michael J; Finlay, Alison L (Investigative ophthalmology & visual science, 2007)
Visual defects associated with amblyopia have been extensively studied, but their impact on the performance of everyday visuomotor tasks is unclear. This study evaluates eye-hand coordination (prehension) skills in adult amblyopes compared with normal subjects. Twenty amblyopes (10 strabismic, 10 nonstrabismic) with different degrees of visual acuity loss (mild, moderate, or severe) and stereodeficiency (reduced or undetectable) participated, along with 20 matched control subjects. Subjects reached, precision grasped, and lifted cylindrical household objects (two sizes, four locations) using binocular vision or just the dominant or amblyopic (nondominant) eye, while the actions of the preferred hand were recorded. Various indices of prehension planning and online control were quantified for all trials (n = 48) performed under each viewing condition. Initial reaching behavior and grip shaping before object contact, which result from movement programming, were relatively normal in the amblyopic subjects, despite their vision losses. By contrast, they exhibited a range of deficits under both binocular and nondominant eye conditions in their final approach to the object (terminal reach) and when closing and applying a grasp. These impairments included prolonged execution times and more errors compared with control subjects, the extents of which covaried with the existing depth of amblyopia, although not with its underlying cause. Visuomotor adaptations in amblyopes are relatively minor and limited to aspects of movement planning. Their deficits in movement execution should benefit, however, from treatments that restore spatial acuity and binocularity to progressively normal levels and so deserve more explicit consideration when assessing therapeutic outcomes.